Human health risk assessment and bioaccumulation of trace metals in fish species collected from the Miri coast, Sarawak, Borneo - Anandkumar, A.; Ramasamy, Nagarajan; Prabakaran, K.; Bing, C.; Rajaram, R. (Elsevier, 2018)
The concentrations of nine trace metals (Cr, Mn, Co, Ni, Cu, Zn, Rb, Cd, and Pb) were measured in different tissues of two pelagic and five demersal fish species collected from the Miri coast, Sarawak. The sequence of accumulation of trace metals in different tissues were: liver > gill > gonad > muscle. Zn (301.00 µg g-1) and Cd (0.10 µg g-1) was the maximum and minimum accumulated elements. According to the Hazard Index calculation, none of the elements will pose any adverse health effects to humans for both ingestion rates (normal and habitual fish consumers) proposed by USEPA, except for Pb and Cd in certain fish species. On the basis of the results, the level of elements in the edible muscle tissues of all the analyzed fish species from the Miri coast are below the maximum permissible limits of Malaysian and International seafood guideline values and safe for consumers.